The evolving position of director of track and field operation - Tape, A. (Techniques Magazine, 2013)
A new and rapidly growing position in the collegiate track and field world has materialized over the course of the past few years. Many of the larger programs now employ a Director of Operations on their staff to handle all of the managerial and organizational tasks that come with conducting a high level program. Having a Director of Operations on staff allows the coaches to specifically focus on coaching and recruting. Director of Operations may be a graduate assistant, part-time, or full-time position, and they may also have coaching responsibilities providing that the program is not at the NCAA limit on number of coaches. The specific responsibilities assigned to an individual in this position will vary based on the structure of the program, the skill set of the employee, and the support of the athletic department. Director of Operations may not seem like a glamorous position in the world of track and field but this individual serves as the main contact for the track and field program and should be philosophically aligned with that of the head coach. In a highly functioning program it is not a simple managerial position; the operations job is administrative in nature and is critical to the success of the program. Almost all combined programs are dealing with 80-100 athletes, six full-time coaches, and six sports throughout the course of the academic year. It is not likely for a team to be successful if the coaches and athletes aren`t in the right place at the right time with the right equipment and it is the responsibility of the Director of Operations to take care of those crucial logistical matters. One can think of the operations positions as being similar to a decathlete. They must be proficient in numerous skills but may have a few main areas of strength where they really excel. In this article, we will examine skills that are helpful for operations professionals to possess as well as some common tasks for which the Director of Operations tends to be responsible. Part I: The Skill Set of a Director of Operations Part II: Possible Responsibilities for Director of Operations